Dawni autorzy o grafomanii - Śnieżko, Dariusz (Przestrzenie Teorii, 2007)
The topic of the article are opinions formulated by old Polish writers on this sort of literary activity (and it's authors) that presently is called "graphomania", in the context of the ancient tradition and some statements expressed by selected European men of letters. At the beginning of the article theoretical conditions are sketched that - according to the author - should be taken into consideration in order to effectively use the terms "graphoman" and "graphomania". Then, on the basis of the literary quotations, there have been distinguished the criteria that in the old writers' eyes seemed the most representative of graphoman's works. In the end are presented the most popular, parodistic means used by the writers to discredit the title phenomena.